Paritas dan Umur dengan Kejadian Sectio Caesarea di Rumah Sakit Muhammadiyah Palembang Tahun 2014 - Septi Purnamasari; Nita (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2018)
Based on data from the World Health Organization (WHO) in 2010, there were 600,000 pregnant women and maternity die each year worldwide. Based on data from the SC Medical Record delivery Muhammadiyah Hospital Palembang, in 2012 there were 173 (8.6%) of 2015 normal deliveries, an increase in the year 2013 there were 325 (16.6%) of normal deliveries in 1961 and in 2014 there were 340 (22.1) of the 1534 normal deliveries. Objective is a known relationship of parity and age at occurrence SC Muhammadiyah Hospital in Palembang 2014. This research used an analytic survey with a cross-sectional approach. The analysis used chi-square. The population in this study is the total number of normal deliveries in Muhammadiyah Hospital Palembang Year 2014 with a sample of 317 respondents by random sampling. Intake through medical records using the checklist, if the data in the analysis of univariate and bivariate. Univariate results obtained respondents who experienced childbirth SC by 175 respondents (55.2%), high parity respondents as many as 161 respondents (50.8%). Age at high risk as much as 187 respondents (59.0%). Results of bivariate with chi-square test on continuity correction, the parity values obtained p-value of 0.02 <α 0.05. At the age obtained p-value value of 0.33 <α 0.05. Means that there is a relationship of parity and age at occurrence Sectio Caesarea. So it is advisable to midwives and health workers to further improve health service delivery in the case of SC.